Study of the structure of hadronic events and determination of αs at √s = 130 GeV and 136 GeV - Dova, María Teresa (1996)
We present a study of the structure of hadronic events recorded by the L3 detector at center-of-mass energies of 130 and 136 GeV. The data sample corresponds to an integrated luminosity of 5 pb-1 collected during the high energy run of 1995. The shapes of the event shape distributions and the energy dependence of their mean values are well reproduced by QCD models. From a comparison of the data with resummed Ο(α2s) QCD calculations, we determine the strong coupling constant to be αs( 133 GeV ) = 0.107 ± 0.005 (exp) ± 0.006( theor).